A ouvidoria pública universitária como instrumento de participação popular: o caso da UTFPR - Sandy, Nelissa Carleto (2013)
The office of ombudsman intermediate communication between citizens and the Administration, based on the constitutional principles of Legality, Impersonality, and Efficiency, acting as an instrument of participation in the democratic management and as lawful representatives to the citizens´ interests. Information access is based on democracy and is enlisted as a constitutional (article 5, XIV e XXXIII of Brazil´s Federal Constitution) and infra-constitutionally (Law nº 12.527, of November 18th, 2011) right. The freedom granted to citizens comprises the participation in the right to access information, especially since it allows popular participation and consequently, makes democracy more dynamic. A well informed society is able to take effective action in the State´s destiny, enforcing the sovereignty of common will. Public participation grants citizen access to governmental management acts, enabling social control over the acts of the State. The hereby paper focus on examining UTFPR´s Ombudsman as an instrument of public participation in administrative management. The present research is exploratory and applied, using a study case as the method. In the data collection, multiple sources of evidence are used: article records, a questionnaire and physical artifacts. The results show that UTFPR´s Ombudsman service demand is rising, regardless of the challenges faced by the office of the Ombudsman while exercising the constitutionally imposed task – little or no physical room, impossibility of full time dedication to the office, among others challenges. The questionnaires answered by Ombudsman officers, former officers and managers enable the researcher to conclude that the Office of the UTFPR Ombudsman is a place of communication between the user and the Administration, an instrument of popular participation in management. However, its autonomy must be strengthened. As a result of the research, the author concludes that the implementation of periodical evaluation by the user/customer; more Ombudsman disclosure; changes in the University´s website concerning the Ombudsman; investment in courses on mediation, are advisable.